Teacher educators' vision of an 'ideal' teacher - Charanjit Kaur Swaran Singh; Nor Azmi Mostafa; Dodi Mulyadi; Noor Alhusna Madzlan; Eng Tek Ong; Siti Shuhaida Shukor; Tarsame Singh Masa Singh (Universitas Syiah Kuala, 2021)
There is no clear definition of what constitutes an ideal teacher educator, particularly from the perspective of Malaysian educators. Developing teacher educators’ vision of an ideal teacher ensures that teachers have high levels of professional, personal, and contextual dimensions in teaching practices, including competence in the practice of professional teaching, knowledge, and understanding. Therefore, the objective of this study was to find out the range of visions of what it is to be a good teacher educator in a Malaysian teacher education institution. Seventeen teacher educators from an established university in Malaysia participated in the study. A survey consisting of eight questions was used as the research instrument. The data obtained from the questionnaire were analysed by using descriptive and textual analysis techniques. The findings reveal certain criteria of an ideal teacher such as possessing sound subject matter knowledge, mastery of both generic and content-specific pedagogy, and hands-on teaching skills. The teacher educators shared that they have to adjust their goals to attain their vision, namely the need to adapt to the current policies, new ideas, and the ever-changing educational trends. The findings also show that an ideal teacher is the one who is responsible to nurture and bring about the best learning experience for students. This research has unfolded the teacher educators’ vision of the ideal teacher and pedagogical implications reflected in every facet of their educational practices.